2021
DOI: 10.3390/ijms22041504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ATR Inhibition in RT Response of HPV-Negative and HPV-Positive Head and Neck Cancers

Abstract: Radiotherapy (RT) has a central role in head and neck squamous cell carcinoma (HNSCC) treatment. Targeted therapies modulating DNA damage response (DDR) and more specific cell cycle checkpoints can improve the radiotherapeutic response. Here, we assessed the influence of ataxia-telangiectasia mutated and Rad3-related (ATR) inhibition with the ATR inhibitor AZD6738 on RT response in both human papillomavirus (HPV)-negative and HPV-positive HNSCC. We found that ATR inhibition enhanced RT response in HPV-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Inhibition of Wee1 by adavosertib was recently described as a highly effective single-agent treatment for HPV-positive HNSCC dependent on FOXM1 activation ( 55 ) and single agent radio- and chemosensitization through PARP, as well as through intra-S/G2 checkpoint inhibition, which was repeatedly demonstrated in HPV-positive HNSCC models ( 10 , 21 23 , 25 , 30 , 31 , 56 , 57 ). In this study we demonstrate a highly effective radiosensitization of HPV-positive HNSCC cells using dual inhibition of PARP and the S/G2 cell cycle checkpoint in five and moderate radiosensitization in one out of six cell lines tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of Wee1 by adavosertib was recently described as a highly effective single-agent treatment for HPV-positive HNSCC dependent on FOXM1 activation ( 55 ) and single agent radio- and chemosensitization through PARP, as well as through intra-S/G2 checkpoint inhibition, which was repeatedly demonstrated in HPV-positive HNSCC models ( 10 , 21 23 , 25 , 30 , 31 , 56 , 57 ). In this study we demonstrate a highly effective radiosensitization of HPV-positive HNSCC cells using dual inhibition of PARP and the S/G2 cell cycle checkpoint in five and moderate radiosensitization in one out of six cell lines tested.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that PARP inhibition as well as inhibition of radiation induced cell cycle checkpoints via targeting of Chk1, ATR, or Wee1 can radiosensitize HPV-positive HNSCC cells (10,(21)(22)(23)(24)(25). Different mechanisms may account for the observed sensitization.…”
Section: Introductionmentioning
confidence: 97%
“…Because CHK1 has been proposed to be a promising target in HNSCC cell cycle regulation, and recent HNSCC studies have shown ATR inhibition to sensitise HPVnegative cells to DDAs, our assumption is encouraging [125,139]. Moreover, other studies have shown synthetic lethal targeting to sensitize HNSCC cells to DDAs with other inhibitors [137,140,141]. Because of this, applying c-MET inhibitors in a synthetic lethal manner could provide an alternate approach for HPV-negative HNSCCs.…”
Section: Targeting the Cell Cycle With Met/hgf Inhibitorsmentioning
confidence: 96%
“…Conceptually, the loss of wild type p53 can be exploited therapeutically by inducing synthetic lethality [135]. By abrogating the G2 checkpoint, mutant or depleted TP53 cells could be sensitised to DDAs -this is because the absence of both G1 and G2 checkpoints cause the segregation of chromosomal aberrations, forcing cells into the M phase to die [136,137]. As stated, in the previous section, in 2010 Medova et al, reported c-MET inhibition to attenuate the ATR-CHK1-CDC25 pathway -responsible for intra-S and G2-M arrest [77].…”
Section: Targeting the Cell Cycle With Met/hgf Inhibitorsmentioning
confidence: 99%
“…M6620 (previously VX-970) is a first-in-class ATR inhibitor currently under investigation in a phase 1 trial in HPV-negative HNSCC (NCT02567422). AZD6738 is another selective ATR inhibitor that was recently demonstrated to enhance radiotherapy response in both HPV-negative and HPV-positive HNSCC in vitro [62]. A clinical trial of AZD6738 plus olaparib is currently ongoing in HNC (NCT02264678), and another biomarker-based study has recently been completed (NCT03022409).…”
Section: Atm/atrmentioning
confidence: 99%